Monetary Implications of Cross-Border Derivatives for Emerging Economies - Mendez Morales, Armando (Washington, D.C. : International Monetary Fund, 2001)
This paper surveys concepts, practices and analytical literature to assess benefits and risks for monetary stability of cross-border currency and interest rate derivative operations in calm and turbulent periods, with a view of extracting implications for emerging economies. Monetary authorities must prevent one-sided positions in the currency, favor asset substitutability, and incorporate the enriched information set provided by derivative-based transactions into monetary policy design. In some circumstances, the use of derivatives by monetary authorities may help fulfill this role. By contrast, surcharges to compensate for a downward impact of derivatives on the cost of capital appear neither advisable nor necessary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet